Nilai-nilai Spiritualitas Pada Peziarah Makam Buyut Entol Sena dan Buyut Entol Dipawana Desa Ciwaru Kecamatan Ciwaru Kabupaten Kuningan - Romantika (UIN Syarif Hidayatullah Jakarta), Genta (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The tradition that has been carried out until now is the practice of visiting graves, traditions that are carried out by visiting family graves, the graves of pious people, the tombs of the clergy, the tombs of saints and tombs that are believed to have an influence on an area. Grave pilgrimage is often an option used as a medium in increasing spiritual awareness when it is still in a stage of internal conflict. This research is qualitative by prioritizing field research. Primary sources obtained through field observations, interviews with caretakers, pilgrims and the surrounding community and documentation. While the secondary data obtained refers to books and various journals that are relevant to this research. The location of this research is in Ciwaru Village, Ciwaru District, Kuningan Regency, West Java. The results of the study show that the Spiritual Values of Grave Pilgrims can be summed up in several opinions, including: Pilgrims make pilgrimages to graves to remember death so as to produce peace in life, pray for goodness for the bodies, increase good deeds and in some opinions believe that the soul or spirit It is eternal and does not perish with the body, so it becomes an intermediary in praying so that it is answered more quickly.